2014
DOI: 10.1111/tpj.12687
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of motifs contributing to the interaction between PLS‐subfamily members and their target RNA sequences in plastid RNA editing

Abstract: SUMMARYIn plant organelles, RNA editing alters specific cytidine residues to uridine in transcripts. Target cytidines are specifically recognized by pentatricopeptide repeat (PPR) proteins of the PLS subfamily, which have additional C-terminal E or E-DYW motifs. Recent in silico analysis proposed a model for site recognition by PLS-subfamily PPR proteins, with a correspondence of one PPR motif to one nucleotide, and with the C-terminal last S motif aligning with the nucleotide at position -4 with respect to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 56 publications
2
49
1
Order By: Relevance
“…The most detailed analysis of RNA binding by PLS-class proteins delimited the minimum binding sites for the editing factors CRR28, OTP85, CRR21, and OTP80 (Okuda et al, 2014). This analysis showed that each of these factors binds an RNA sequence containing approximately as many nucleotides as the factor contains PPR motifs, evidence in favor of one motif:one nucleotide binding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most detailed analysis of RNA binding by PLS-class proteins delimited the minimum binding sites for the editing factors CRR28, OTP85, CRR21, and OTP80 (Okuda et al, 2014). This analysis showed that each of these factors binds an RNA sequence containing approximately as many nucleotides as the factor contains PPR motifs, evidence in favor of one motif:one nucleotide binding.…”
Section: Discussionmentioning
confidence: 99%
“…Position 6 appears to be important for distinguishing between purines (A, G) and pyrimidines (U, C), while position 19 directs recognition of amino (A, C) or keto (G, U) groups (Yagi et al, 2013). Most of these correspondences are based on statistical correlations in alignments between PPR binding factors and their RNA targets, but only a few combinations have been confirmed experimentally, and these only for P motifs, and only in vitro (Barkan et al, 2012;Okuda et al, 2014). Based on statistical correlations, S motifs appear to deviate from the P motif code in some important respects and L motifs differ substantially from P and S motifs at the key position 6 (Barkan et al, 2012;Takenaka et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Members of the PLS subfamily of pentatricopeptide repeat (PPR) motif-containing proteins are trans-factors that specifically recognize ciselements (Kotera et al, 2005;Zehrmann et al, 2009). The recognition code that specifies how PPR proteins interact with cis-elements was proposed recently based on in silico analysis and interactions were confirmed by RNA-protein binding assays (Barkan et al, 2012;Takenaka et al, 2013;Yin et al, 2013;Okuda et al, 2014). Many editing PPR proteins contain a C-terminal DYW domain (Lurin et al, 2004).…”
mentioning
confidence: 98%
“…The 2nd, 5th, and 35th (or 1st, 4th, and 34th or 3rd, 6th, and 1st in other numbering systems) residues at each repeat are considered to be RNA selection "codes" (9-11). Based on these codes, several PPR proteins have been successfully modified to recognize predictable RNA targets (9,(12)(13)(14)(15)(16)(17).The small MutS-related (SMR) domain was originally identified at the C terminus of MutS2 in the cyanobacterium Synechocystis (18). SMR proteins are widely distributed in almost all organisms (19).…”
mentioning
confidence: 99%